Effect of Lanthanum as a Promoter on Fe-Co/SiO2 Catalyst for Fischer-Tropsch Synthesis - Ali Abbasi; Mohamadreza Ghasemi; Sepehr Sadighi (Bulletin of Chemical Reaction Engineering & Catalysis, 2014)
Iron-Cobalt catalyst is well known from both operational and economical aspects for Fischer-Tropsch synthesis. Effort to increase the efficiency of this kind of catalyst is an important research topic. In this work, the effect of lanthanum on characteristic behavior, conversion and selectivity of a Fe-Co/SiO2 Fischer-Tropsch catalyst was studied. The Fe-Co-La/SiO2 Catalysts were prepared using an incipient wetness impregnation method. These catalysts were then characterized by XRF-EDAX, BET and TPR techniques, and their performance were evaluated in a lab-scale reactor at 250ºC, H2/CO = 1.8 of molar ratio, 16 barg pressure and GHSV=600 h-1. TPR analysis showed that the addition of La lowered the reduction temperature of Fe-Co catalyst, and due to a lower temperature, the sintering of the catalyst can be mitigated. Furthermore, from the micro reactor tests (about 4 days), it was found that lanthanum promoted catalyst had higher selectivity toward hydrocarbons, and lower selectivity toward CO2. © 2014 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0)